Comics and narration - Groensteen, Thierry (University Press of Mississippi, 2013)
This book is the follow-up to the author's previous work, in which the leading French-language comics theorist set out to investigate how the medium functions, introducing the principle of iconic solidarity, and showing the systems that underlie the articulation between panels at three levels: page layout, linear sequence, and nonsequential links woven through the comic book as a whole. He now develops that analysis further, using examples from a very wide range of comics, including the work of American artists such as Chris Ware and Robert Crumb.